Language Strategies in Tourism: Analysing Code-Switching Among Sasak Tour Guides on Social Media - Putri Nila Sudewi Ni Ketut; Rukmana Fachrul Islam; Titik Ceriyani Miswaty; Suparlan Suparlan; Abdurrahman Shaleh Reliubun (CV. ULIL ALBAB CORP, 2024)
Social media have transcended their role as mere communication tools, evolving into dynamic spaces where intricate sociolinguistic behaviors are reflected. Lenhart (2020) identified platforms such as Instagram, TikTok, and X becoming integral to daily communication and identity expression. It has facilitated cultural exchange and created opportunities for multilingual communication. This study examines the language strategies employed by Indonesian tour guides on social media, focusing on the phenomenon of code-switching and its functions proposed by Hoffman's (1991). The findings found there were three types of code switching used, such as intra-sentential, inter-sentential, and tag switching. The most type of code switching uttered by the guide is intra-sentential switching. The function is to incorporating local terms and switching languages, they add cultural nuance, emphasize key points, engage the audience, and vividly convey specific behaviors.